Rare earth microalloying corrosion-resistant wear-resistant coiled plate NM400 and manufacturing method thereof
Through ultra-pure steel smelting and hot rolling, the structure and composition of NM400 coil plates are controlled, and the problems of the existing NM400 coil plates are solved, thus achieving high efficiency and low cost Production of rare earth microalloy corrosion-resistant wear-resistant coil plates.
Patent Information
- Application Number
- CN202411429270.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-14
AI Technical Summary
When the current NM400 coil plate is transformed at mid-temperature temperature, the proportion of ferrite on the surface of the steel strip is relatively high, resulting in a reduced wear resistance. At the same time, the cooling of the rear section leads to greater internal stress on the coil and difficult to control the plate shape.
Through ultra-pure steel smelting, continuous casting and hot rolling controlled rolling, the product is mainly composed of needle bainite, and solid solution strengthening, fine crystal strengthening and precipitation strengthening are used to match 2250mm thermal mechanical controlled rolling and cold-controlled process to manufacture rare earth microalloy corrosion-resistant wear-resistant coil NM400.
It achieves good regulation of product strength, toughness, weather resistance and wear resistance, reduces production costs, improves production efficiency, and has good plate control, which is suitable for mass production.
Smart Images

Figure CN119464957A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallurgical materials, and specifically relates to a rare earth microalloyed corrosion-resistant wear-resistant coil NM400 and a manufacturing method thereof, and more particularly to a thin-gauge (4-8mm) corrosion-resistant, wear-resistant, high-strength NM400 hot-rolled steel strip and a manufacturing method thereof. Background Art
[0003] Search for patents and literature currently involved in related fields:
[0004] Patent CN 114058814 B (hereinafter referred to as document 1) discloses "a method for preparing NM400 wear-resistant steel with high hardness uniformity". The product composition design includes: C: 0.20-0.40%, Mn: 1.20-1.80%, Si: 0.20-0.50%, Cr: 0.20-0.60%, Mo: 0.20-0.50%, Al: 0.02-0.04%, Ti: 0.01-0.02%, P: ≤0.02%, S: ≤0.02%; B: 0.0001-0.0025%, and the rest is Fe and unavoidable impurity elements. The preparation method of document 1 mainly includes slab smelting casting, rolling, pre-straightening, cooling and tempering processes, and the key temperature control is: the final rolling temperature is 930℃~980℃, the end temperature of pre-straightening is 850℃~880℃, and the tempering temperature is 200℃~400℃. It belongs to the production process of medium and thick plates, and the product composition design adds precious alloy element Mo, which is relatively costly.
[0005] Patent CN 111440996 B (hereinafter referred to as Document 2) discloses "A 6-8mm TMCP online quenching low yield ratio high strength wear-resistant steel NM400 coil and its production method", and its composition design system is that the steel contains C: 0.18-0.22%, Si: 0.30-0.50%, Mn: 1.30-1.45%, P: ≤0.012%, S: ≤0.003%, Nb: 0.015-0.025%, Ti: 0.010-0.025%, Cr: 0.25-0.40%, B: 0.0005-0.0020, Ca: 0.0010-0.0030%, Al: 0.020-0.050%, H: ≤2ppm, O: ≤30ppm, N: ≤50ppm, and the balance is Fe and unavoidable impurities. This document 2 uses continuous casting slabs and 2250mm rolling mill controlled rolling and cooling technology to complete the production of NM400 coils, and realizes the control of ferrite and martensite microstructures through double-stage cooling. Its shortcomings are: after the front-stage cooling, when the medium-temperature ferrite transformation is entered, the proportion of ferrite on the surface of the steel strip is higher than that in the core, and the wear resistance is reduced; on the other hand, the rear-stage cooling enters low-temperature coiling (coiling temperature ≤200℃), which leads to large internal stress in the steel coil and poor plate shape control.
[0006] Patent CN 115896621 A (hereinafter referred to as Document 3) discloses "a thin-gauge high-quality plate-shaped NM400 steel plate produced by online quenching process and its manufacturing method". The product composition design includes: C: 0.14-0.18%, Si: 0.40-0.80%, Mn: 1.20-1.50%, Alt: 0.055-0.085%, Nb: 0.010-0.020%, Cr: 0.65-0.85%, Ti: ≤0.005%, V: ≤0.010%, Ni: ≤0.10%, Cu: ≤0.10%, Mo: ≤0.10%, P: ≤0.012%, S: ≤0.001%, N: ≤40ppm, and the rest are Fe and unavoidable impurity elements. Online quenching replaces offline quenching process, which belongs to the production process of medium and thick plates, and the production cost is relatively high. Summary of the invention
[0007] Based on the above technical background, the present invention successfully realizes the control of the product's microstructure mainly composed of needle-shaped bainite through the controlled rolling and cooling control technology of ultra-pure steel smelting, continuous casting and hot rolling, and achieves a reasonable match of product strength, toughness, weather resistance and wear resistance by means of solid solution strengthening, fine grain strengthening and precipitation strengthening as the main means. Based on this product control strategy, a rare earth micro-alloyed corrosion-resistant wear-resistant coil NM400 and a manufacturing method thereof are provided. The product composition design system is (0.16-0.22%) C-(1.00-1.50%) Si-(1.20-1.50%) Mn-(≤0.020%) P-(≤0.005%) S-(0.030-0.060%) Als-(0.010-0.030%) Nb-(0.020-0.050%) Ti-(1.00-1.50%) Cr-(0.002-0.005%) La-(0.0008-0.0015%) B, H≤2ppm, O≤25ppm, N≤60ppm. The smelting process adopts hot metal pretreatment - converter smelting - refining outside the furnace (LF+RH) - slab continuous casting, and the rolling adopts the controlled cooling process of 2250mm hot rolling unit (slab heating - rough rolling - finishing rolling - layer cooling - coiling). The mechanical properties of the product meet the yield strength: 900~1100MPa, tensile strength: 1250~1400MPa, elongation A 50 : 12-18%, yield strength ratio: 0.70-0.79; Brinell hardness: 380-420, grain size ≥10. 72-hour periodic immersion corrosion, the corrosion rate of the test steel is ≤60% compared with the corrosion rate of Q355B. The addition of rare earth La on the one hand alleviates the central segregation of high-alloy ingots and increases the proportion of equiaxed crystals; on the other hand, rare earth La interacts with alloy Cr to change the corrosion potential and the properties of corrosion products to enhance the corrosion resistance of the product. Therefore, the product has good toughness, weather resistance and wear resistance. The production process adopts the conventional domestic 2250mm production. The process is relatively simple and executable, the product production efficiency is high, the cost is relatively economical, and it is suitable for enterprise batch stable production. The present invention is specifically implemented through the following technical solutions.
[0008] In a first aspect, the present invention provides a rare earth microalloyed corrosion-resistant wear-resistant coil NM400, whose chemical composition is calculated by mass percentage: C 0.16-0.22%, Si 1.00-1.50%, Mn 1.20-1.50%, P≤0.020%, S≤0.005%, Als0.030-0.060%, Nb 0.010-0.030%, Ti 0.025-0.050%, Cr 1.00-1.50%, B 0.0008-0.0015%, La0.0020-0.0050%, H≤2ppm, O≤25ppm, N≤60ppm, and the rest is Fe and unavoidable inclusions.
[0009] In some embodiments, the chemical composition of the rare earth microalloyed corrosion-resistant wear-resistant coil NM400 is calculated by mass percentage: C 0.18-0.20%, Si 1.25-1.45%, Mn 1.25-1.45%, P≤0.020%, S≤0.005%, Als0.030-0.050%, Nb 0.015-0.020%, Ti 0.025-0.045%, Cr 1.35-1.50%, B 0.0012-0.0014%, La0.0020-0.0035%, H≤2ppm, O≤25ppm, N≤60ppm, and the rest is Fe and unavoidable inclusions.
[0010] In some embodiments, the mechanical properties of the rare earth microalloyed corrosion-resistant wear-resistant coil NM400 meet the following requirements: yield strength: 900-1100 MPa, tensile strength: 1250-1400 MPa, elongation A 50 : 12~18%, yield strength ratio: 0.68~0.78; Brinell hardness: 380~420, grain size ≥10 level.
[0011] In some embodiments, the corrosion rate of the rare earth microalloyed corrosion-resistant wear-resistant coil NM400 in a 72-hour periodic immersion corrosion test is ≤60% compared to the corrosion rate of Q355B.
[0012] In some embodiments, the rare earth microalloyed corrosion-resistant wear-resistant coil NM400 has a thickness of 4 to 8 mm.
[0013] In a second aspect, the present invention provides a method for manufacturing rare earth micro-alloyed corrosion-resistant wear-resistant coil NM400, which includes a smelting continuous casting process and a rolling process.
[0014] In some embodiments, the smelting and continuous casting process is: molten iron → molten iron pretreatment → converter steelmaking → LF refining → RH degassing → slab continuous casting; wherein the converter smelting adopts KR pre-desulfurized molten iron (molten iron [S] ≤ 0.002%), ferrosilicon, ferromanganese and ferrochrome are added after the converter taps out steel, ferroniobium is added at the end of LF refining, and ferrotitanium is added at the end of vacuum degassing treatment to adjust to the alloy addition target value, La-Fe alloy is added before vacuum treatment negative pressure, the air breaking treatment is ended after circulating for 3 minutes, and the ladle is directly put into the casting machine for casting without Ca treatment; argon is blown and stirred throughout the molten steel process; vacuum degree ≤ 2mbar, treatment time ≥ 10min, superheat ΔT ≤ 30-40°C, and continuous casting billet stretching is 1.2-1.5m / min; equipped with dynamic soft pressure technology, and the straightening temperature ≥ 800°C.
[0015] In some embodiments, the rolling process is: slab heating - high-pressure water descaling - fixed-width press - E1R1 roughing mill rolling - E2R2 roughing mill rolling - flying shear - high-pressure water descaling - F1~F7 finishing mill rolling - encrypted laminar cooling - coiling - pallet transportation system - warehouse stacking slow cooling - sampling and inspection; wherein the slab heating temperature is 1245±20℃; heating time is 180~240min; rough rolling mode adopts 1+5, 3+3 or 3+5; intermediate billet thickness range: 35~40mm; finishing rolling start temperature ≤1080℃; finishing rolling final rolling temperature is 840~900℃, coiling temperature is 450~550℃, and cooling rate is 30~50℃ / s.
[0016] The advantages of the present invention are:
[0017] The present invention provides a C-Si-Mn-Cr-Ti-Nb-B-La microalloying composition design, which matches the 2250mm thermomechanical controlled rolling and controlled cooling process to manufacture rare earth microalloyed corrosion-resistant wear-resistant coil NM400. The design advantage is that under the TMCP process conditions, medium-temperature coiling is adopted to obtain NM400 hot-rolled coils mainly composed of needle-shaped bainite, which has good plate shape control and low stress control, and breaks through the industry problem of low production efficiency and high manufacturing cost of thin-gauge wear-resistant plates produced by offline heat treatment. In the production practice of the 2250mm hot rolling production line, it has good cost advantages and promotion value. Compared with the above-mentioned documents 1-3, the present invention focuses on adding unconventional alloy Si and Cr elements and rare earth La alloys, and the conventional laminar cooling of the hot rolling 2250mm unit realizes medium-temperature coiling, completes the smooth coiling of NM400 coils, and further releases deformation profit through high-temperature coiling. Achieve good regulation of product strength, toughness, weather resistance and wear resistance, as well as low-cost control. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The metallographic structures of the rare earth microalloyed corrosion-resistant wear-resistant coil NM400 produced in Example 1 at 1 / 4 thickness (A) and the center of thickness (B).
[0019] Figure 2 These are the bending performance (180°) test results of the rare earth microalloyed corrosion-resistant wear-resistant coil NM400 produced in Example 2, wherein A and B represent views in different directions. DETAILED DESCRIPTION
[0020] The present invention designs a thin-gauge NM400 hot-rolled steel strip with a main component system of C-Si-Mn-Ti-Nb-Cr-La-B to meet the trend of developing new steel materials that are corrosion-resistant and wear-resistant for carriage bodies in the service environment of slag transportation. The material design is based on the necessary solid solution strengthening effect of C and Mn elements and the low control level of harmful elements S and P. Adding a high content of Si element, solid solution strengthening, and cooperating with Al element can inhibit the precipitation of cementite within a certain temperature range, which is conducive to the formation of acicular bainite during medium-temperature transformation; adding a high content of Cr element, the hardenability of the material is improved through solid solution, and the precipitated carbides improve the wear resistance and corrosion resistance. Adding Nb element plays a role in fine grain strengthening to improve the toughness of the material, and Ti element plays a role in dispersion precipitation strengthening to greatly improve the strength of the material. At the same time, adding rare earth La, using its high-temperature precipitation of the second phase to refine the cast structure and improve the finished product band structure, thereby improving the toughness of the wear-resistant steel strip. Specifically:
[0021] 1. Material composition control: as shown in Table 1 below, the C content is controlled at 0.16% to 0.22% (preferably 0.18% to 0.20%) to ensure material strength and wear resistance; the Si content is controlled at 1.00% to 1.50% (preferably 1.20% to 1.40%), and in conjunction with the Als (content 0.045% to 0.060%) element, the precipitation of cementite can be inhibited within a certain temperature range, which is conducive to the formation of acicular bainite during medium-temperature transformation; the Mn content is controlled at 1.20% to 1.50% (preferably 1.25% to 1.45%) to ensure material toughness and wear resistance; the Cr content is controlled at 1.00% to 1.50% (preferably 1.25% to 1.50%), Improve the hardness and wear resistance of the material; Nb content is controlled at 0.010% to 0.030%, and the grains are refined, which can improve the impact toughness and toughness of the steel; Ti content is controlled at 0.020% to 0.050% (preferably 0.025% to 0.045%), precipitation strengthening, and coordinated with Nb to strengthen the fine grains, improve the wear resistance of the material; B content is controlled at 0.0008% to 0.0015% (preferably 0.0010% to 0.0014%), to improve the hardenability of the material; rare earth La content is controlled at 0.0020% to 0.0050%, and the second phase is precipitated at high temperature to refine the cast structure and improve the finished product band structure, thereby improving the toughness and corrosion resistance of the wear-resistant steel strip. Element P is controlled at ≤0.020%; S content is controlled at ≤0.005%, which is a harmful element and needs to be effectively controlled; gas in steel is controlled at H≤2ppm, O≤25ppm, and N≤60ppm.
[0022] Table 1: Composition design (mass percentage)
[0023]
[0024] 2. Material smelting
[0025] 2.1. Converter smelting: The pre-treated molten iron (S≤0.002%) enters the converter, where oxygen is blown for decarburization and temperature is raised. In the later stage of smelting, ferrosilicon and ferromanganese are added for deoxidation and alloying. The P and S components are controlled to prevent overoxidation of the molten steel and the amount of steel tapping is controlled to prevent slag from entering the molten steel. The tapping temperature is 1600-1650°C. The converter tapping has [P]≤0.020%, [S]≤0.006%. Alloys Si, Mn and Cr are added during the tapping process.
[0026] 2.2. Refining outside the furnace: LF+RH full argon blowing process is adopted, a good reducing atmosphere is maintained during the refining process, Al wire is used for deoxidation, LF is used to add ferromanganese and ferroniobium for alloying, RH vacuum treatment (vacuum degree ≤ 2mbar, deep vacuum time ≥ 10min), and ferrotitanium, ferroboron and rare earth lanthanum iron are added for alloying in the later stage, and no calcium treatment is performed after completion.
[0027] 2.3. Slab continuous casting: Use special protective slag, molten steel superheat ΔT≤30~40℃, casting speed controlled at 1.20~1.50m / min. Equipped with dynamic soft reduction technology, straightening temperature ≥800℃.
[0028] 2.4. Full nitrogen control: N≤60ppm in the tundish of molten steel, scrap ratio≤90%, converter tapping temperature≥1600℃, bottom blowing argon stirring in the converter, bottom blowing stirring mode with argon and nitrogen switching alternately cannot be used. The ladle is emptied with argon, argon is used to purge the tundish for ≥10min before continuous casting and heat exchange to exhaust the air in the ladle, and when the tundish pours 30t, the argon blowing tube is removed to reduce nitrogen absorption by the molten steel, and argon blowing is used to protect the casting during the normal casting process.
[0029] 3. Controlled rolling and controlled cooling process
[0030] The ingot is heated in a walking-beam heating furnace (the heating process is shown in Table 2). The rough rolling adopts single-stand R1 and R2 reciprocating rolling. The rough rolling modes adopted are 1+5, 3+3 and 3+5. The finishing rolling adopts F1~F7 continuous rolling process. The specific controlled rolling and controlled cooling process is shown in Table 3.
[0031] Table 2: Billet heating system
[0032]
[0033] Table 3: Rolling system
[0034]
[0035] Material purity control: Ultra-purity control and organizational uniformity control of materials are the basis for ensuring that the materials have good resistance to hydrogen embrittlement. Through the smelting and double refining process, the product's non-metallic inclusions A, B, C, D levels are ≤1.5, and the sum of non-metallic inclusion levels is ≤2.5.
[0036] Material structure morphology control: the structure grain size is ≥10, and the core-surface structure grain size difference is ≤2. The structure is mainly composed of acicular bainite and supplemented by granular bainite, with acicular bainite accounting for 70% to 80% and banded structure ≤1.5.
[0037] The present invention is described in detail below through specific examples. The examples are intended to help understand the present invention but are not intended to limit the present invention.
[0038] According to the above smelting technical requirements, the ingots with the following compositions are smelted. The specific compositions are shown in Table 4 below.
[0039] Table 4: Chemical composition of each example (mass percentage: %)
[0040]
[0041] The smelting and hot rolling processes are designed according to the above composition (as shown in Table 5 below), and the mechanical properties of the products are shown in Table 6.
[0042] Table 5: Smelting and rolling process parameters of Examples 1-3
[0043]
[0044] Table 6: Product performance of each embodiment
[0045]
[0046]
[0047] The product is based on the standard TB / T 2375-1993 "Cyclic Infiltration Corrosion Test Method for Weathering Steel for Railways". After the corrosion test, the surface macroscopic morphology is observed and the corrosion rate of the experimental steel is calculated. The experimental solution is 0.01mol / L NaHSO3 solution, the pH value is controlled within 4.4-4.8, and the replenishing solution is 0.02mol / L NaHSO3 solution. The experimental temperature is (45±2)℃, the humidity is (70±5)%RH, and the baking temperature is required to be (70±5)℃. 72 hours of periodic infiltration corrosion, the corrosion rate of the test steel of Examples 1-3 is ≤60% compared to the corrosion rate of Q355B. The results are shown in Table 7 below.
[0048] Table 7: Relative corrosion rates of various examples
[0049]
[0050] The results in Table 7 above show that the corrosion rate of the test steel in the embodiment is ≤60% compared with the corrosion rate of Q355B.
[0051] The metallographic structure of the material of Example 1 is analyzed to be mainly acicular bainite, supplemented by granular bainite; the grain size is ≥10, and the banded structure is ≤1.5. Figure 1 As shown, frame A represents the metallographic structure morphology of 1 / 4 of the thickness, and frame B represents the metallographic structure morphology of the center of the thickness.
[0052] The bending performance (180°) of the material of Example 2 was analyzed, and the results were as follows: Figure 2 As shown, A and B represent views in different directions, and it can be seen that the bending performance of the modified material is good.
[0053] In summary, the invented material has good strength, toughness, corrosion resistance and wear resistance, and can be promoted and applied in large quantities in the field of lightweight and long-life steel for slag dump trucks.
[0054] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A rare earth microalloyed corrosion-resistant wear-resistant coil NM400, whose chemical composition is calculated by mass percentage: C0.16-0.22%, Si 1.00-1.50%, Mn 1.20-1.50%, P≤0.020%, S≤0.005%, Als 0.030-0.060%, Nb0.010-0.030%, Ti 0.025-0.050%, Cr 1.00-1.50%, B 0.0008-0.0015%, La 0.0020-0.0050%, H≤2ppm, O≤25ppm, N≤60ppm, and the rest is Fe and unavoidable inclusions.
2. The rare earth microalloyed corrosion-resistant wear-resistant coil NM400 according to claim 1, wherein the chemical composition is calculated by mass percentage as follows: C 0.18-0.20%, Si 1.25-1.45%, Mn 1.25-1.45%, P≤0.020%, S≤0.005%, Als0.030-0.050%, Nb 0.015-0.020%, Ti 0.025-0.045%, Cr 1.35-1.50%, B 0.0012-0.0014%, La0.0020-0.0035%, H≤2ppm, O≤25ppm, N≤60ppm, and the rest is Fe and unavoidable inclusions.
3. The rare earth microalloyed corrosion-resistant wear-resistant coil NM400 according to claim 1 or 2 has the following mechanical properties: yield strength: 900-1100 MPa, tensile strength: 1250-1400 MPa, elongation A 50 : 12~18%, yield strength ratio: 0.68~0.78; Brinell hardness: 380~420, grain size ≥10 level.
4. The rare earth microalloyed corrosion-resistant wear-resistant coil NM400 according to any one of claims 1 to 3, wherein the corrosion rate thereof in a 72-hour periodic immersion corrosion test is ≤60% compared with the corrosion rate of Q355B.
5. The rare earth microalloyed corrosion-resistant wear-resistant coil NM400 according to any one of claims 1 to 4, wherein the thickness is 4 to 8 mm.
6. The method for manufacturing the rare earth microalloyed corrosion-resistant wear-resistant coil NM400 according to any one of claims 1 to 5, comprising a smelting continuous casting process and a rolling process.
7. The manufacturing method according to claim 6, wherein the smelting and continuous casting process is: molten iron → molten iron pretreatment → converter steelmaking → LF refining → RH degassing → slab continuous casting; wherein the converter smelting adopts KR pre-desulfurized molten iron (molten iron [S] ≤ 0.002%), ferrosilicon, ferromanganese and ferrochrome are added after the converter taps out steel, ferroniobium is added at the end of LF refining, and ferrotitanium is added at the end of vacuum degassing treatment to adjust to the alloy addition target value, La-Fe alloy is added before vacuum treatment negative pressure, the air-breaking treatment is ended after circulating for 3 minutes, and the ladle is directly put into the casting machine for casting without Ca treatment; argon is blown and stirred throughout the molten steel process; vacuum degree ≤ 2mbar, treatment time ≥ 10min, superheat ΔT ≤ 30-40°C, and continuous casting slab is stretched 1.2-1.5m / min; equipped with dynamic soft reduction technology, and the straightening temperature ≥ 800°C.
8. The manufacturing method according to claim 6 or 7, wherein the rolling process is: slab heating - high-pressure water descaling - fixed-width press - E1R1 roughing mill rolling - E2R2 roughing mill rolling - flying shear - high-pressure water descaling - F1~F7 finishing mill rolling - encrypted laminar cooling - coiling - pallet transportation system - warehouse stacking slow cooling - sampling and inspection; wherein the slab heating temperature is 1245±20℃; the heating time is 180~240min; the rough rolling mode adopts 1+5, 3+3 or 3+5; the intermediate billet thickness range is: 35~40mm; the finishing rolling start temperature is ≤1080℃; the finishing rolling final rolling temperature is 840~900℃, the coiling temperature is 450~550℃, and the cooling rate is 30~50℃ / s.
Citation Information
Patent Citations
Process for the preparation of sulphur from claus off-gases
CA1000030A
High strength and toughness abrasion-resistant and corrosion-resistant bainite steel rail for heavy haul railway and manufacturing method of steel rail
CN108385022A
Corrosion-resistant high-strength and toughness wear-resistant bainite steel rail and production method thereof
CN108531833A
High-performance and hot-rolled wear-resistant steel sheet and production method thereof
CN111254351A
Rare earth wear-resistant steel NM400 coiled plate with excellent low-temperature-resistant toughness and production method of thereof
CN112322976A